Role of histamine-mediated macrophage differentiation in clearance of metastatic bacterial infection - Kim, Kwang H.; Park, Donghwan; Cho, Soo Young; Cho, Yejin; Lee, Buhyun; Jeong, Haengdueng; Lee, Yura; Lee, Yourim; Nam, Ki Taek (Frontiers in Immunology, 2023)
Macrophages are highly heterogeneous immune cells with a role in maintaining tissue homeostasis, especially in activating the defense response to bacterial infection. Using flow cytometric and singlecell RNA-sequencing analyses of peritoneal cells, we here show that small peritoneal macrophage and immature macrophage populations are enriched in histamine-deficient (Hdc -/-) mice, characterized by a CD11b mi F4/80 lo CCR2 + MHCII hi and CD11b lo F4/80 mi THBS1 + IL-1 + phenotype, respectively. Molecular characterization revealed that immature macrophages represent an abnormally differentiated form of large peritoneal macrophages with strong inflammatory properties. Furthermore, deficiency in histamine signaling resulted in significant impairment of the phagocytic activity of peritoneal macrophage populations, conferring high susceptibility to bacterial infection. Collectively, this study reveals the importance of histamine signaling in macrophage differentiation at the molecular level to maintain tissue homeostasis, offering a potential therapeutic target for bacterial infection-mediated diseases.